Detecção e afinamento de bordas em direções previamente conhecidas - Artero, Almir Olivette [UNESP]; Tommaselli, Antonio Maria Garcia [UNESP] (My University, 2009)
This work presents a study on the generation of digital masks aiming at edge detection with previously known directions. This solution is important when edge direction is available either from a direction histogram or from a prediction based on camera and object models. A modification in the non-maximum suppression method of thinning is also presented enabling the comparison of local maxima for any edge directions. Results with a synthetic image and with crops of a CBERS satellite images are presented showing an example with its application in road detection, provided that directions are previously known.
Detection and thinning of edges in previously known directions
Keywords: Adaptative edge detection; Segmentation; Thinning